The Watershed as a Conceptual Framework for the Study of Environmental and Human Health - Alan S. Kolok; Cheryl L. Beseler; Xun-Hong Chen; Patrick J. Shea (SAGE Publishing, 2009)
The watershed provides a physical basis for establishing linkages between aquatic contaminants, environmental health and human health. Current attempts to establish such linkages are limited by environmental and epidemiological constraints. Environmental limitations include difficulties in characterizing the temporal and spatial dynamics of agricultural runoff, in fully understanding the degradation and metabolism of these compounds in the environment, and in understanding complex mixtures. Epidemiological limitations include difficulties associated with the organization of risk factor data and uncertainty about which measurable endpoints are most appropriate for an agricultural setting. Nevertheless, it is our contention that an adoption of the watershed concept can alleviate some of these difficulties. From an environmental perspective, the watershed concept helps identify differences in land use and application of agrichemicals at a level of resolution relevant to human health outcomes. From an epidemiological perspective, the watershed concept places data into a construct with environmental relevance. In this perspectives paper, we discuss how the watershed can provide a conceptual framework for studies in environmental and human health.